Educational Games as Learning Process for Children - Kurniasih, Dewi; Ika, E C (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to introduce learning educational games that teach numbers, colors, animals, musical instruments, letters, shapes, fruits, and transportation. The method used in this study was the waterfall method. The results showed us that the children, in general, like to play. It was hoped that this educational game could increase children’s enthusiasm for learning and improve the learning process. This was because the development of children and the development of technology were very fast, and Android system-based educational game was made to help the learning process of children bored in learning. Children’s learning is no longer monotonous with this educational game, they can learn and play at the same time.